Recurrence of Atrial Tachyarrhythmia During the Second Month of the Blanking Period Is Associated With More Extensive Pulmonary Vein Reconnection at Repeat Electrophysiology Study. (August 2015) - Das, Moloy; Wynn, Gareth J.; Morgan, Maureen; Lodge, Ben; Waktare, Johan E.P.; Todd, Derick M.; Hall, Mark C.S.; Snowdon, Richard L.; Modi, Simon; Gupta, Dhiraj
<x xml:space="preserve">Abstract</x> Background— Current guidelines recommend a 3-month blanking period after pulmonary vein isolation (PVI) as early recurrence of atrial tachyarrhythmia (ERAT) may be due to transient proarrhythmic factors. However, studies have suggested that these factors resolve by 1 month. PV reconnection (PVrc) is strongly associated with postblanking AT recurrence in paroxysmal atrial fibrillation. We hypothesized that ERAT occurring beyond 4 weeks after PVI is associated with PVrc at repeat electrophysiology study. Methods and Results— Forty patients with paroxysmal atrial fibrillation underwent mandatory repeat electrophysiology study 2 months after PVI, regardless of symptoms, to document the number of reconnected PVs. Antiarrhythmic drugs, including β-blockers, were discontinued 4 weeks after PVI. Patients were instructed to record a 30-second ECG everyday between the 2 procedures using a portable monitor, with additional recordings for symptoms. ERAT was defined as ≥30 seconds of AT. Patients recorded a total of 3293 ECGs. Four (10%) patients had ERAT in the first 4 weeks (M1) only, 2 (5%) in month 2 (M2) only, and 11 (28%) in both. PVrc of 1 PV was identified in 12 (30%) patients and of >1 PV in 13 (32%) patients. ERAT in M2 was associated with PVrc, whereas M1 was not (11/13 [85%] versus 0/4 [0%]; P=0.006). M2 ERAT was strongly associated with PVrc of >1 PV (10/13 [77%] versus 3/27 [11%] without M2 ERAT; P<0.0001). Conclusions— ERAT occurring beyond 4 weeks after PVI is associated with PVrc and particularly of PVrc of >1 PV. ERAT confined to M1 is unrelated to underlying PVrc. The relationship between ERAT beyond 4 weeks after PVI and postblanking AT recurrence merits further investigation.